Strategy of Actors SMES during COVID-19 in Strengthening Regional Economy - Khairuna Khairuna; Asnariza Asnariza; Rahmah Yulianti (International Conference on Multidisciplinary Research, 2022)
This study aims to examine strategies for SMEs actors during COVID-19. COVID-19 has had impacts on various sectors, especially in economic sector. COVID-19 in Banda Aceh has effect not only in health sector but also in education sector and in economic sector (in their business sectors especially for SMEs). Because of the reason a strategy is needed to maintain SMEs business in the midst of this pandemic. This research was conducted during the COVID-19 pandemic in the period from March to December 2020. The research method used in this study is a qualitative analysis with applying an exploratory step and with participatory observation techniques. The analytical method used is a descriptive approach that identifies various problems faced by SMEs, analyzes the problems, and formulates a strategy model to overcome the problems. Result of this study recommends a strategy for SMEs in adapting any changes that occur through a new strategy to support development of local SMEs. The development strategy is analyzing the strategy by using SWOT analysis. The analysis relies on technology to reach consumers and adjust consumers’ condition to sale of products and services. The survival strategy is implementing ECommerce, digital marketing, product quality improvement, service quality improvement, and Customer Relations Marketing (CRM).The results of this study are important to be understood and adopted by SMEs and it is hoped that SME actors will always be responsive to adapt to environmental changes so that they still enable to survive and also still strengthen regional economy and then experience growth. Keywords: SME Strategy, Strengthening regional economy, COVID-19